Automation of Urban Infrastructure Based on Predictive Maintenance and IoT - Starykova, S. (My University, 2025)
Modern cities face challenges related to the operation and maintenance of critical infrastructure, including transport networks, energy systems and water supply facilities. The use of Predictive Maintenance technologies in combination with the Internet of Things (IoT) allows ensuring the uninterrupted operation of urban systems, increasing resource efficiency and reducing repair and maintenance costs. The article discusses the concept of Predictive Maintenance for urban infrastructure, the principles of its implementation and the impact on the sustainability of urban development.
Keywords: Predictive Maintenance; urban infrastructure; Smart City; digital transformation